Potential of native weed species as nutrient contributors of coconut garden in an Entisol - Mathew, Jeena; Krishnakumar, V.; Namboothiri, C.G. Narayanan (Journal of Plantation Crops, 2014)
Potential of native weed species as nutrient contributors of coconut garden in an Entisol